Factors Related to Exclusive Breastfeeding in East Java – Indonesia - Mohamad Yoto; Hario Megatsari; Azizah Andzar Ridwanah; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2022)
Exclusive Breast Feeding (EBF) is very crucial for the growth and development of toddlers in the future, both physically and mentally. The study aims to analyze factors related to EBF in East Java, Indonesia. The analysis material for the study was the 2017 Indonesian Nutritional Status Monitoring, a cross-sectional survey. In East Java, the study obtained 3977 toddlers using the multi-stage cluster random sampling process. The study used binary Logistic Regression tests to interpret the data. The results show for toddlers living in cities have a 0.951 times lower probability of experiencing EBF than toddlers residing in rural areas. Toddler age (in months) is one of the determinants of EBF. All categories of maternal marital status are more likely than mothers who are never married to having an EBF toddler. All maternal education levels have a better chance than mothers who have no education to have EBF children. Except for mothers in the senior high school category, which has no significant relationship with the incidence of EBF in children under five in East Java, Indonesia. The study also found toddler’s age associated with the incidence of EBF in children under five in East Java, Indonesia. Finally, the toddler boy has a probability of 0.943 times compared to the toddler girl to experience EBF in East Java in Indonesia. The study concluded that six variables were related to the incidence of EBF in East Java - Indonesia, namely residence, mother’s age, mother’s marital, mother’s education, toddler’s age, and toddler’s gender.